Reporte de Fusarium moniliforme var. subglutinans sobre piña en Cuba - Perez Peñaranda, M.C.=700 1 Borras Hidalgo, O.; Arzola Gonzalez, M.; Rodriguez, Y.
(En, Es)
Ilus., 11 ref.
Keywords: GIBBERELLA FUJIKUROI; ORGANISMOS PATOGENOS; SINTOMAS; PODREDUMBRES; PIÑA; CUBA